Los contratos temporales: exposición y crítica - Pasco Cosmópolis, Mario (2012)
Temporary contracts: exposition and criticThe contract of term or fixed term or determined period constitutes one of the most frequent modalities of so-called atypical contracting. EfrénCórdova, in his famous presentation at XI World Congress of the International Society for Labor Law and Social Security (Caracas 1985), noted that, being typical the contract celebrated between an employer and a worker, to be executed to full time at the center of work and for an indefinite atypicalperiod, comes to be one that lacks any of these attributes, this is: (i) in which involves more than one employer, or (ii) the journey is partial or doesn’t fit to traditional parameters of eight hours per day and forty-eight a week at most, or (iii) performs out the usual local, or (iv) is for adefined time. It is about these lasts that is dedicated the present article.